Respuesta :
Note: Your function is missing some information. It seems your function is
[tex]f\left(x\right)=\frac{-3}{x}+7[/tex].
So, I am solving the question based on the function [tex]f\left(x\right)=\frac{-3}{x}+7[/tex], because it would still solve your query.
Answer:
Please see the explanation.
Step-by-step explanation:
Given the function
[tex]f\left(x\right)=\frac{-3}{x}+7[/tex]
A function g is the inverse of a function f for y = f(x), x=g(y)
[tex]y=\frac{-3}{x}+7[/tex]
Replace x with y
[tex]x=\frac{-3}{y}+7[/tex]
solve for y
[tex]y=-\frac{3}{x-7}[/tex]
so the inverse of [tex]f\left(x\right)=\frac{-3}{x}+7[/tex] will be:
[tex]f^{-1}\:\left(x\right)=-\frac{3}{x-7}[/tex]
Finding the domain of [tex]f^{-1}\:\left(x\right)=-\frac{3}{x-7}[/tex]
As we know that domain is the set of the possible input values where the function is defined.
so the function domain must be: [tex]x<7\quad \mathrm{or}\quad \:x>7[/tex]
Therefore,
[tex]\mathrm{Domain\:of\:}\:-\frac{3}{x-7}\::\quad \begin{bmatrix}\mathrm{Solution:}\:&\:x<7\quad \mathrm{or}\quad \:x>7\:\\ \:\mathrm{Interval\:Notation:}&\:\left(-\infty \:,\:7\right)\cup \left(7,\:\infty \:\right)\end{bmatrix}[/tex]